Memahami Esensi Tauhid Melalui Al-Qur’an - Tanjung, Alwin Tanjung (Al-Kauniyah, 2023)
This journal aims to explore and understand the essence of monotheism, a basic concept in the Islamic religion, through the guidance of the Koran. Tawhid refers to the monotheistic belief that underlies Islamic teachings, namely belief in the oneness of Allah. The Koran, as the holy book in Islam, is the main source for understanding the concept of monotheism. This journal explores various verses of the Koran that discuss monotheism, providing a deep understanding of the oneness of Allah and its implications in everyday life. In the theological dimension, tawhid emphasizes the recognition of the existence of Allah as the creator of the universe and the regulator of all affairs. This understanding encourages Muslims to worship and submit completely to His will. Ethically, monotheism motivates individuals to live in accordance with Islamic moral and ethical values, due to awareness of the omniscient and just supervision of Allah. The meaning of monotheism as an integral concept in Islam provides a foundation for a strong religious and moral life. Understanding monotheism not only creates a close relationship between humans and Allah, but also encourages Muslims to become agents of positive change in society. Therefore, understanding and implementing monotheism is the key to forming strong character and morality for Muslims.